Being Survive During Pandemic: The Analysis Character Strength and Health Related Quality of Life in Covid-19 Survivors - Umniyah Saleh; Nur Fajar Alfitra; Muhammad Ikhsan Rahmat; Nur Faizah; S. Nurul Azizah; Miskah Ramdhani M; Haiqal Aliftiansyah Ma'rufi (Universitas Ahmad Dahlan, 2021)
This research focuses on picturing the characters strength among covid-19 survivors regarding to their HRQOL’ level. This research used a quantitative method with a cross-sectional survey design, with WHOQOL-BREF scale and VIA Strength Classification System as measurement tools. The sampling method was purposive sampling, with the criteria of the respondent are have been infected by the SARS-Cov-2 and living in Makassar City. There are 52 respondents were selected for the analysis process. The present study found that hope is one of the influential factors on HRQOL based on the rank order. The hope rank significantly increased along with the level of HRQOL. Thus, the development of rank in hope characters, it can be concluded that hope is an important character for covid-19 survivors in increasing their Health-Related Quality of Life (HRQOL). Keywords: Character Strength, Health Related Quality of Life, Covid 19 Survivors